THE EFFECT OF HOT WATER SUPPLY TO THE LEVEL OF FORMALIN AND PROTEIN IN THE TERI FISH - Ira Oktaviani Rz (INDONESIA NATURAL RESEARCH PHARMACEUTICAL JOURNAL, 2018)
Formalin (formaldehyde) is a colorless or almost colorless solution with a pungent odor, its vapor stimulates the membranes of the nose and throat liver, and burning. The use of Formalin as a food preservative is prohibited by the government, since this material is toxic. However, from the survey results are still found some types of foods containing formalin. Formalin has the ability to preserve food because aldehyde groups that are easy to react with proteins to form methylen compounds, so as to reduce protein levels in food. This study aims to examine the effect of long periods of hot water immersion on decreased levels of formalin and increased protein levels in anchovies. The qualitative test of formalin content in anchovy was done by color reaction method using Schiff reagent and quantitative assay of determination of formalin and protein content was done by Schiff and Biuret method as measured by UV-Vis spectrofometer. From the results of the study found that there is a decrease in formalin levels and increased protein content in anchovy with an increase in the time immersion with hot water.